Replay : memoir of an uprooted family - Mechner, Jordan (First Second, an imprint of Roaring Book Press, 2024)
"In this intergenerational graphic memoir, renowned video game designer Jordan Mechner traces his family's journey through war, Nazi occupation, and everyday marital strife."--Amazon.